RB714, RB715, RB716, RB717 and RB718 antibodies recognize the histone HMtA protein from Methanobrevibacter smithii by ELISA - Hammel, Philippe; Pick, Horst; Sutherland, Duncan Bruce (Antibody Reports, 2022)
The recombinant antibodies RB714, RB715, RB716, RB717 and RB718 detect by ELISA the M. smithi histone HMtA protein fused to a GST.